Improvement of an electro‐thermal model of SiC MPS diodes. Issue 4 (1st April 2018) - Starzak, Łukasz; Stefanskyi, Andrii; Zubert, Mariusz; Napieralski, Andrzej
Abstract : This study presents improvements introduced in a behavioural electro‐thermal model of silicon carbide merged PIN‐Schottky (SiC MPS) diodes, aimed at a better representation of device characteristics for a more accurate prediction of power dissipation. In the electrical domain, the junction capacitance model has been thoroughly validated with a new parameter extraction procedure, yielding realistic values of the turn‐off charge as well as current and voltage waveforms for various operating conditions, which is crucial for dynamic loss evaluation. The validity of the thermal sub‐model has been extended by reflecting the temperature dependence of thermal conductivity. As a result, temperature evolution on both the long and short time scales is properly computed, providing correct on‐state voltage drop and on‐state power loss results. Device behaviour with a heat sink attached is also correctly simulated.